Energy taxes and employment: a do-it-yourself simulation model - Christoph Böhringer; Anna Ruocco; Wolfgang Wiegard (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
Our paper deals with the welfare and employment effects of green tax reforms. In the first part we develop a flexible, interactive simulation model which is accessible under http://brw.zew.de. Users can specify their own green tax reforms or emission quotas and quantify welfare and employment effects. He or she can choose between different model variants, e. g. closed or small open economies with or without unemployment. In the second part we describe the numerical model specifications and explain some simulation calculations by means of examples. Some exercises for classroom use are available on the above mentioned web-site.
Keywords: 330; Ökosteuer; Energiesteuer; Steuerreform; Simulation; Wirtschaftspolitische Wirkungsanalyse; Planspiel; Theorie